Determinant Online Consumption Emotion on Fashion Brand Muslim in Indonesia - Rahmawati, Nur Fitri; Santoso, Teguh; Setiawan, Irfan (Jurnal Manajemen Bisnis, 2024)
This research predicts that online consumption emotions are understood through five levels, excitement, comfort, ecstasy, annoyance, and romance. This research aims to provide deeper insight into the behavior of Muslim fashion consumers in general. This research uses a quantitative approach with the research object being all online Muslim fashion consumers in Indonesia. This research uses Structural Equation Model (SEM) analysis with smart-PLS. The results of the study show the highest score on the joy dimension indicating that this factor has the most significant impact on influencing online consumption emotions. Other highs are comfort and ecstasy, but the lows are annoyance and romance. Based on The results of research on online consumption emotions that have been measured and analyzed, it provide a strong indication that excitement has the most dominant impact on shaping online consumption emotions.